THE ACCEPTANCE OF EDUCATION GAME AS LEARNING MEDIA OF INDONESIAN CULTURE FOR PRIMARY SCHOOL STUDENTS - Candra Dewi; Rekyan Regasari Mardi Putri (Journal of Innovation and Applied Technology, 2016)
Indonesia is a country known for its cultural diversity. Getting to know the culture of a nation which starts from an early age is needed to foster national values to form the nation's character. However, the cultural lesson is not a favorite subject for student todays. For this reason, we need efforts to bring the matter of culture to be fun and interesting to learn. Related to primary school students, the ways of learning by playing is much preferred. Recently, the game can be simulated by using computer technology. Therefore, it is possible to develop computer games based learning media. The activities carried out in this community service activity include the design and manufacture of culture learning games package. After that, the training about using the game as learning media is conducted for primary school teacher. Based on the analysis results of a questionnaire given during training showed that the game are made is easy to operate, to understand and to play. Similarly, the benefits provided are considered significant in terms of giving out a fun learning experience, helping to evaluate learning outcomes and decent used to support teaching and learning process.